Tislelizumab plus chemotherapy versus chemotherapy as first-line treatment for extensive-stage small cell lung cancer: A cost-effectiveness analysis - Zhiwei Zheng; Huide Zhu; Ling Fang (PLoS ONE, 2025)
Objective This study aims to conduct a cost-effectiveness analysis of tislelizumab in combination with platinum and etoposide compared to the standard treatment of etoposide and platinum as first-line therapy for extensive-stage small cell lung cancer(ES-SCLC) from the Chinese medical system perspective. Methods A partitioned survival model was developed utilizing data from the RATIONALE-312 trial to accurately simulate the clinical and economic outcomes of both treatment arms. This model incorporates three distinct health states, namely progression-free survival, disease progression, and death. These states are exclusive of each other, and patients can transition between them as their disease progresses.The model accounted for various cost components such as drug therapy, management of adverse events, disease progression, and overall survival. To evaluate the cost-effectiveness of the interventions, quality-adjusted life-year (QALY) and incremental cost-effectiveness ratio (ICER) were chosen as the metrics. The analysis employed a willingness to pay (WTP) threshold of $39,855.79 per QALY. Additionally, sensitivity analyses were conducted to assess the robustness and reliability of the model. Results The tislelizumab group had a total cost of $52,749.69, whereas the chemotherapy group’s total expenses amounted to $8,811.62. Additionally, the tislelizumab group experienced a gain of 2.21 QALY compared to the chemotherapy group, albeit incurring an additional cost of $43,938.07. Consequently, this led to an ICER of $19,881.48, which falls below the Chinese WTP threshold of $39,855.79. Sensitivity analyses confirmed the robustness of the findings across a range of scenarios. Conclusion This cost-effectiveness analysis based on the RATIONALE-312 trial demonstrates that tislelizumab plus platinum and etoposide is a cost-effective treatment option for ES-SCLC compared to the standard chemotherapy from the Chinese medical system perspective.